A liberdade em A montanha mágica - Abrahão, Thiago Henrique De Camargo [UNESP] (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/; Programa de Pós-Graduação em Língua e Literatura Alemã, 2020)
Amid the hilly landscape of the Swiss Alps, a sanatorium for respiratory diseases. The many coughs in long treatment do not have more serious commitments than following the usual mealtime and home schedule. Faced with this spatially stagnant and temporally hermetic medium of Thomas Mann’s The magic mountain, freedom is muffled. We do not refer, of course, to the creative freedom of the German author, whose proof of grandeur is the novel itself, neither to the interpretative freedom of the reader, but to freedom -or rather its attenuation- problematized by the characters of this long history. This is the case of the young protagonist Hans Castorp, whose learning about the theme paradoxically occurs at the time of his stay in a place that hijacks his freedom. This is not only because the main character is unable to choose, without constraints, the values ​​that underlie his choices, but also because this is hampered by the anomalous, or, according to the title, “magic” spatio-temporal situation of the mountain. How this problem is presented narratively, by means of some freedom indexes - that is, elements that modify the indeterminacy of the narrative, for the characters and the reader -, is what we want to present.

Em meio à paisagem montanhosa dos Alpes suíços, um sanatório para doenças respiratórias. As muitas tosses ali em longo tratamento não possuem compromissos mais sérios que não sejam seguir o horário habitual das refeições e dos repousos. Diante desse meio espacialmente estagnado e temporalmente hermético de A montanha mágica, de Thomas Mann, a liberdade mostra-se amortecida. Não nos referimos, evidentemente, à liberdade criativa do autor alemão, cuja prova de grandeza é o romance em si, tampouco à liberdade interpretativa do leitor, mas à liberdade - ou, antes, sua atenuação - problematizada pelas personagens dessa longa história. É o caso do jovem protagonista Hans Castorp, cujo aprendizado a respeito do tema paradoxalmente ocorre durante sua estada num lugar que sequestra sua liberdade. Isso se dá não apenas porque a personagem principal é incapaz de eleger, sem constrangimentos, os valores que embasam suas escolhas, mas também porque isso é dificultado pela situação espaçotemporal anômala ou, segundo o título, “mágica” da montanha. Como essa problemática é apresentada narrativamente, por meio de alguns índices de liberdade - ou seja, elementos que modificam, para as personagens e para o leitor, a indeterminação da narrativa -, é o que queremos apresentar.
Freedom in The magic mountain
Keywords: literary theory; freedom; The magic mountain; teoria literária; liberdade; A montanha mágica